Explaining compliance: Lessons learnt from civil and political rights - Çali, Basak; Koch, Anne (Cambridge University Press, 2017)
Introduction The enforcement of economic, social and cultural (ESC) rights judgments is often considered to present challenges that are different from those encountered in the realm of civil and political (CP) rights. Linking in with a growing literature on the judicial enforcement of ESC rights (Merali and Oosterveld, 2001; Dixon, 2007; Gauri and Brinks, 2008; Gloppen, 2009; Langford, 2008; Rodríguez-Garavito, 2011), this edited volume as a whole is based on the assumption that there is something particular about the implementation of ESC rights that is worth investigating. Notwithstanding the well-founded claims underlying this assumption, this chapter takes a step back and asks what lessons from the implementation of international CP rights judgments might be generalised and fruitfully applied to the broader field of international human rights implementation, including the realm of ESC rights. The chapter’s key contribution to the discussion of enforcement is achieved through a shift of focus: rather than concentrating on the type of judgment to be enforced and presuming that the content of the right in question will determine the success or failure of its enforcement, this chapter looks at the process of human rights judgment implementation as such – taking into consideration the costs of compliance and how these costs can be moderated by the institutional design of enforcement regimes. The analysis focuses on international adjudication but draws partly on comparative research, and its findings are relevant to the national level. It proposes an interactional framework for understanding human rights judgment implementation in which the speed and comprehensiveness of domestic human rights judgment enforcement is determined by the interaction between international human rights bodies and national decision makers, and argues that the process through which the terms of implementation are defined is of crucial importance. The chapter illustrates this argument through the analysis of the enforcement regime in place for the judgments of the European Court of Human Rights, where a ‘deliberative enforcement model’ is used to mitigate the domestic costs of compliance with complex CP rights remedies. The overall analysis suggests that the realm of CP rights enforcement offers important lessons for identifying and overcoming challenges to the enforcement of ESC rights.
CRIS-Team Scopus Importer:2023-03-21